If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4x = 3x + -7 Reorder the terms: 3 + 4x = -7 + 3x Solving 3 + 4x = -7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 4x + -3x = -7 + 3x + -3x Combine like terms: 4x + -3x = 1x 3 + 1x = -7 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 1x = -7 + 0 3 + 1x = -7 Add '-3' to each side of the equation. 3 + -3 + 1x = -7 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = -7 + -3 1x = -7 + -3 Combine like terms: -7 + -3 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| 2(4x+9)=-78 | | (x-2)2+x(x-3)=3(x+4)(x-3)-(x+2)(x-1)+2 | | 3a^3-4a=0 | | 9c^2+6c=0 | | .66x+5=.33x+14 | | 3(8-7x)=-207 | | 4a^3-a=0 | | -5(2x+1)=-45 | | 2(2+5x)=-66 | | 4(2z-2)=7(z-4) | | (8x^3-7x^2+10x-9)-(2x^3-5x^2-8x+9)= | | 13=x+18 | | x^5(2-x)=0.98 | | 6(10+2x)=60 | | 30d^2+37d+10=0 | | -3(-7x+6)=-270 | | 7(3x-7)=-70 | | 7(-6x+4)=-434 | | 7x+5y=10000 | | 9+4m=2m-15 | | 9(4m)=2m-15 | | x=51/3+87/12 | | a^2-a^4=0 | | 0.5-x=0.28x | | -35+23=-6x+10x | | 5p^2+10=16p | | 6(-6x+1)=-102 | | 9x^2-12x+6xy-8y=0 | | 8cos^4(x)+2cos^2(x)=3 | | 0=-4x^2+2x+2 | | f(x)=2x^2+7x+3 | | 0=-4x^2+5x+9 |